Endoscopic Mucosal Healing Predicts Favorable Clinical Outcomes in Inflammatory Bowel Disease: A Meta-analysis. Issue 8 (August 2016) - Reinink, Andrew R.; Lee, Terrence C.; Higgins, Peter D. R.
Abstract : Background: Mucosal healing (MH) in inflammatory bowel disease has been associated with improved long-term clinical outcomes. Uncertainty remains as to the magnitude of this effect and to how this association changes with time and degree of healing. Methods: PubMed, EMBASE, and Web of Science searches identified 1570 citations. Screening of abstracts identified 155 articles for full-text review, of which 19 met inclusion criteria. For 3 outcomes of interest (surgeries, hospitalizations, remission), weighted random-effects meta-analysis was performed. Results: In pooled analysis, MH predicted fewer major abdominal surgeries (relative risk [RR], 0.34; 95% confidence interval [CI], 0.26–0.46), increased remission (RR, 1.84; 95% CI, 1.43–2.36), and fewer hospitalizations (RR, 0.58; 95% CI, 0.42–0.78). Complete MH and partial MH both showed significantly higher rates of favorable outcomes. Separate analyses for Crohn's disease and ulcerative colitis showed identical patterns for surgeries and remission. When subjects with no healing were excluded, and complete versus partial healing was compared, rates of surgery were not significantly different (RR, 0.82; 95% CI, 0.46–1.44). However, complete healing was superior in predicting corticosteroid-free remission (RR, 1.71; 95% CI, 1.24–2.34). Meta-regression found that the predictive power of this complete versus partial healing distinction was strongly associated with the duration of follow-up after endoscopy. Conclusions: MH is a strong predictor of fewer surgeries, long-term clinical remission, and fewer hospitalizations. Complete healing is not significantly more favorable than partial healing for predicting surgeries or hospitalizations, but it did predict higher rates of clinical remission. This benefit of complete MH over partial healing increases with follow-up time. Abstract : Supplemental Digital Content is Available in the Text.